In the Quest for a Different World: Viramma and the Depictions of Dalit Womanhood. Issue 1 (May 2020) - Basu, Raj Sekhar
The article deals with the life experiences of a Dalit woman Viramma, who hails from an interior rural locality of Tami Nadu bordering Pondicherry. In course of her daily conversations with Josiane Racine, a French ethnomusicologist, Viramma shares the different facets of her life, which is conditioned by her own caste and class locations. Viramma's narrative is very different from the version of the Western-educated or the English-educated Indian feminist activists and scholars who often rule out the compromises which seem to be favoured by Viramma and many of her generation. As the wife of a Dalit agricultural worker and herself also employed in the same sort of labouring occupation, Viramma seems to come out often with two apparently contradictory sets of responses, one of protest and the other of reconciliation. She makes it amply clear that as a Paraiyar woman living on the wages offered by the powerful Reddiar landlords, it is difficult to think of creating a situation of the world being turned upside down. This possibly encourages her to look into the other sides of life whether it be that of developments in familial life, ceremonies, rituals or that of popular beliefs centring around ghosts and goblins. Viramma also talks of politics and proves beyond all doubt that the Dalit women do not always need the agency of feminist activists belonging to the privileged groups to voice their protests.